The Rio Olympics: A Triumph of Sportsmanship and Sustainability - SHIPRA JOSHI (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Athletes from all over the world get together at the Olympics to participate in a variety of sports. The games were organized to honour lord Zeus in Greek Culture, where the event has a long and rich history. It is a significant international athletic event. Lately, the Olympics are a symbol of worldwide solidarity and collaboration. Here, athletes represent their nations and compete in a spirit of healthy rivalry. It shifts between the summer and winter seasons every two years, and the event is held after every four years. The latest Olympics, that is, Rio Olympics was held in Brazil in the year 2016 and it was one of the most controversial Olympic Games in history. (Fuller et al., 2017) This research paper will provide an overview of the Rio Olympics. The actual games are then addressed, along with the performances of individual athletes, any controversies that occurred during the competitions, and the event’s overall success. It will discuss the gathered information on each nation's population and GDP as well as the number of medals it has achieved. The research aimed to find out whether a country's Olympic performance and its population or gross domestic product (GDP) were related. It will also discuss the number of games being played and the total number of events in which how many athletes are participating. The core part of the paper will discuss about the impact (both negative and positive repercussions) of the Olympics on the host country, Brazil.(Rosa et al., 2016)